Colombia : Implementing a Collective, Standardized Approach to Catastrophe Insurance of Public Buildings - World Bank (Washington, DC, 2015)
The World Bank has been assisting the Government of Colombia (GoC) since 2012 in the preparation and implementation of an integrated Disaster Risk Financing and Insurance (DRFI) strategy. One component of DRFI strategy seeks to mitigate the fiscal impact of disaster-related losses from damage to public buildings, by increasing insurance coverage. The World Bank has worked with the GoC to design and implement a collective, standardized approach to insurance requirements of public buildings and their contents. This approach will help ensure standard, tailored, insurance coverage for government buildings. A pilot program will be implemented covering twenty-two central government entities.